EXAMINATION OF RE.UNIQLO CAMPAIGN, AIRISM LIFEWEAR PRODUCT QUALITY, AND BRAND COLLABORATION ON PURCHASE DECISION OF UNIQLO PRODUCT - Fahera, Nabila; Rahmiati, Filda; Jamal, Fauziah Nur; Bakri, Mohammed Hariri (President University, 2024)
Fashion trends are inherently present in people’s life. Uniqlo is a distinctive Japanese fashion company that emphasizes innovation and implements its own marketing approach. This study seeks to examine Re.Uniqlo Campaign, AIRism Lifewear Product, and Brand Collaboration on Purchase Decision of Uniqlo Product Through Purchase Intention. This study employs a quantitative research methodology and utilizes primary data for data collecting. The demographic comprises individuals over 17 years old residing in Indonesia who are aware of the sustainability campaign (Re.Uniqlo) and have previously bought products labelled AIRism or collaborative items. This study used a non-probability sampling approach, with a total sample of 152 individuals. The data gathering method is a Google Form questionnaire distributed via social media, with data analysis conducted using SmartPLS 4.0. The data reveal that the Sustainability Campaign, Product Quality, and Brand Collaboration significantly influence Purchase Decisions. Furthermore, Sustainability Campaign significantly influences Purchase Decisions through Purchase Intention. However, Purchase Intention has insignificant influence as a mediator of Product Quality and Brand Collaboration on purchasing decisions.